2004
DOI: 10.1139/o04-006
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of heme oxygenase in the blood vessel wall during atherogenesis

Abstract: Several lines of evidence suggest that antioxidant processes and (or) endogenous antioxidants inhibit proatherogenic events in the blood vessel wall. Heme oxygenase (HO), which catabolizes heme to biliverdin, carbon monoxide, and catalytic iron, has been shown to have such antioxidative properties. The HO-1 isoform of heme oxygenase is ubiquitous and can be increased several fold by stimuli that induce cellular oxidative stress. Products of the HO reaction have important effects: carbon monoxide is a potent va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 103 publications
1
30
0
Order By: Relevance
“…The gene with the greatest level of increase in response to oxLDL was heme oxygenase 1 (HMOX1) ( Table 4). Several lines of evidence suggest that HMOX1 expression can be increased several fold by stimuli that induce cellular oxidative stress, including oxidized LDL (29,30). HMOX1 induction is known to lead to an increase in catalytic free iron release.…”
Section: Genes Uniquely Regulated By Ox-ldlmentioning
confidence: 99%
“…The gene with the greatest level of increase in response to oxLDL was heme oxygenase 1 (HMOX1) ( Table 4). Several lines of evidence suggest that HMOX1 expression can be increased several fold by stimuli that induce cellular oxidative stress, including oxidized LDL (29,30). HMOX1 induction is known to lead to an increase in catalytic free iron release.…”
Section: Genes Uniquely Regulated By Ox-ldlmentioning
confidence: 99%
“…Induction of HO-1 by either genetic approaches or pharmacological intervention has been shown to be effective in preventing or treating pulmonary hypertension in animal models [18,19]. Indeed, several studies support the notion [19] that HO-1 exerts an essential protective role in the vessel wall during atherogenesis [20,21]. However, the mechanism underlying the protection of endothelial cells by HO-1 from TNF-α-induced cytotoxicity remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been postulated that mild to moderate elevations of homocysteine in the general population predispose to atherosclerosis in a manner akin to the classic risk factors (Hackam & Anand, 2003). Additionally, the adaptive and protective responses of arterial vasculature against oxidative stress are important in the prevention of atherosclerosis (Hoekstra et al, 2004).…”
Section: Platelet-related Factorsmentioning
confidence: 99%
“…The heme oxygenase responsible for the degradation of heme grouping of hemoglobin is a stress inducible enzyme with antioxidative properties . The products of its reaction (bilirubine, carbon monoxide and iron) develop a potential protective role against atherosclerosis (Hoekstra et al, 2004). Studies have suggested that different circulating forms of bilirubin have the capacity to remove a variety of reactive species of oxygen, and inhibit the oxidation of LDL particles and the chemotaxis of monocytes, all of which are crucial steps in atherogenesis (Ghem et al, 2010).…”
Section: Oxidative Stress and Bilirubinmentioning
confidence: 99%